2021
DOI: 10.1130/g49458.1
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic origin of the mercury anomalies at the Cretaceous-Paleogene transition of Bidart, France

Abstract: The timing and mechanisms of the climatic and environmental perturbations induced by the emplacement of the Deccan Traps large igneous province (India) and their contribution to the Cretaceous-Paleogene (K-Pg) mass extinction are still debated. In many marine sediment archives, mercury (Hg) enrichments straddling the K-Pg boundary have been interpreted as the signature of Deccan Traps volcanism, but Hg may also have been derived from the Chicxulub (Mexico) impact. We investigated the Hg isotope composition, as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 35 publications
1
4
0
1
Order By: Relevance
“…Hg derived from direct volcanic emission is thought to have no measurable MIF (i.e., Δ 199 Hg, Δ 200 Hg = ∼0‰, Thibodeau & Bergquist, 2017;Zambardi et al, 2009), consistent with a recent estimate of the Δ 199 Hg value of the primitive mantle (0.00 ± 0.10‰, Moynier et al, 2021). Therefore, near-zero Δ 199 Hg values recorded for rock samples in the geologic record have been interpreted as reflecting unaltered volcanic Hg input to the depositional environment (e.g., Font et al, 2021;Thibodeau et al, 2016;Yager et al, 2021;H. Zhang, Zhang, & Shen, 2021).…”
Section: Hg Isotopessupporting
confidence: 69%
See 1 more Smart Citation
“…Hg derived from direct volcanic emission is thought to have no measurable MIF (i.e., Δ 199 Hg, Δ 200 Hg = ∼0‰, Thibodeau & Bergquist, 2017;Zambardi et al, 2009), consistent with a recent estimate of the Δ 199 Hg value of the primitive mantle (0.00 ± 0.10‰, Moynier et al, 2021). Therefore, near-zero Δ 199 Hg values recorded for rock samples in the geologic record have been interpreted as reflecting unaltered volcanic Hg input to the depositional environment (e.g., Font et al, 2021;Thibodeau et al, 2016;Yager et al, 2021;H. Zhang, Zhang, & Shen, 2021).…”
Section: Hg Isotopessupporting
confidence: 69%
“…Hg derived from direct volcanic emission is thought to have no measurable MIF (i.e., Δ 199 Hg, Δ 200 Hg = ∼0‰, Thibodeau & Bergquist, 2017; Zambardi et al., 2009), consistent with a recent estimate of the Δ 199 Hg value of the primitive mantle (0.00 ± 0.10‰, Moynier et al., 2021). Therefore, near‐zero Δ 199 Hg values recorded for rock samples in the geologic record have been interpreted as reflecting unaltered volcanic Hg input to the depositional environment (e.g., Font et al., 2021; Thibodeau et al., 2016; Yager et al., 2021; H. Zhang, Zhang, & Shen, 2021). Alternatively, near‐zero Δ 199 Hg values have also been interpreted as reflecting Hg contributions from a combination of terrestrial and oceanic Hg reservoirs (e.g., J. Shen, Chen, et al., 2019; J. Shen et al., 2021; X. Wang, Cawood, Zhao, Zhao, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that Hg geochemistry is complex and can be easily interfered with by local factors, rendering the use of Hg enrichment ineffective in tracing volcanism (Jin et al., 2023; Them et al., 2019). These factors include the transport pathway (Font et al., 2022; Liu et al., 2021), early diagenetic processes, and excessive TOC levels (Frieling et al., 2023). Charbonnier et al.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies have shown that Hg geochemistry is complex and can be easily interfered with by local factors, rendering the use of Hg enrichment ineffective in tracing volcanism (Jin et al, 2023;Them et al, 2019). These factors include the transport pathway (Font et al, 2022;Liu et al, 2021), early diagenetic Paleoceanography and Paleoclimatology 10.1029/2023PA004762 processes, and excessive TOC levels (Frieling et al, 2023). Charbonnier et al (2020), evaluating the potential role of intense weathering and postdepositional organic matter (OM) degradation on the Hg/TOC, show that postdepositional degradation of marine OM type II to type III may largely modify the amount and the quality of OM.…”
Section: Geochemical Proxiesmentioning
confidence: 99%
“…Massive volcanism due to large igneous provinces has been associated with several mass extinction events but individual large explosive volcanoes can also cause regional to global environmental perturbations beyond climate change (Williams et al, 1992;Wignall, 2001Wignall, , 2005Ward, 2009;Black et al, 2012Black et al, , 2014Grasby et al, 2013Grasby et al, , 2019Spalletti & Limarino, 2017;Osipov et al, 2020;Racki, 2020;Cui et al, 2021;Font et al, 2022;Shen et al, 2022). Kutterolf et al (2013) suggest large explosive volcanoes can inject appreciable enough volumes of bromine and chlorine into the atmosphere that substantially deplete the stratospheric ozone layer on regional scale.…”
mentioning
confidence: 99%